20 mm lithium button battery causing an oesophageal perforation in a toddler: lessons in diagnosis and treatment. Issue 8 (1st May 2012) - Soccorso, Giampiero; Grossman, Ole; Martinelli, Massimo; Marven, Sean S; Patel, Kirtik; Thomson, Mike; Roberts, Julian P
Abstract : Swallowed button batteries (BB) which remain lodged in the oesophagus are at risk of serious complications, particularly in young children. The authors report a 3-year-old child, who rapidly developed an oesophageal perforation, following the ingestion of a 20-mm lithium BB which was initially mistaken for a coin. A thoracotomy and T-tube management of the perforation led to a positive outcome. BBs (20 mm) in children should be removed quickly and close observation is required as the damage initiated by the battery can lead to a significant injury within a few hours.